Human height preferences as a function of population size in the Cook Islands and Norway. Issue 3 (3rd December 2019) - Sorokowski, Piotr; Oleszkiewicz, Anna; Sorokowska, Agnieszka; Pisanski, Katarzyna
Abstract: Objectives: Height preferences and mating patterns related to body size vary across cultures yet it remains unclear why such between‐population differences exist. Here, we test a hypothesis that nonrandom assortative mating is negative (mating with nonsimilar partners) in small isolated populations, and positive (mating with similar partners) in larger populations. Methods: We compared preferences for sexual dimorphism in stature (SDS, male height/female height) among men and women living in small isolated communities (as few as 60 inhabitants) vs larger urban areas (as many as 70 000 inhabitants). To increase generalizability, data were collected from heterogeneous populations in the South Pacific (Rarotonga vs Palmerston, Cook Islands) and Northern Europe (capital city of Tromsø vs villages in the Troms County of Norway). Results: Norwegians preferred a significantly larger difference in height between partners (median SDS ratio of 1.14) than did Cook Islanders (median SDS ratios of 1‐1.04). Indeed, while 30% of Cook Island men and women preferred a partner of the exact same height, this preference was observed among less than 3% of Norwegian men and 7% of Norwegian women. Critically, distributions in SDS preferences did not differ by sex or population size. Thus, rural and urban dwellers within both countries showed similar positive assortative preferences for height, wherein own height explained up to 62% of the variability in preferred partner height. Conclusions: Our results do not support negative assortative preferences in small‐scale communities, and further indicate that the "male‐taller norm, " while weaker among Cook Islanders than Europeans, is observed to some extent in the South Pacific.